Andreas von Hermonthis und das Kloster des Apa Hesekiel Mikrohistorische Untersuchungen zu Kirchengeschichte und Klosterwesen im Gebiet von Armant (Oberägypten) in byzantinischer Zeit anhand der koptischen Ostraka der Universitätsbibliothek Leipzig (O.Lips.Copt. II) - Krueger, Frederic (De Gruyter, 2020)
Based on the edition of nearly 600 Coptic ostraca, Frederic Krueger undertakes a papyrological examination of the Upper Egyptian monastery of Apa Ezekiel. Documents on daily life yield "micro-historical" impressions of socioeconomic aspects of monastic life along with "macro-historical" details of the life of Apa Andrew - priest, abbot, bishop, and "father of all the monks of the ecumene" (apparently: a superregional administrator of the monasteries)
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Sep 2020)
Keywords: Hermonthis, Andreas von -- ca. Ende 6./Anfang 7. Jh.; Universitätsbibliothek Leipzig; Kirchengeschichte 300-600; Geschichte 560-590; Andreas von Hermonthis; Byzantine Studies; Church History; Coptology; Epigraphy; Papyrology; Ägyptisches Mönchtum; HISTORY / Ancient / Egypt; Koinobitentum; Kloster; Ostrakon; Sammlung; Koptisch; Armant; Hochschulschrift